Analgesic and anti-inflammatory effects of hydroalcoholic extract of Astragalus ibrahimianus (Bangladesh Journal of Pharmacology, 2023)
This study aims to investigate the analgesic, anti-inflammatory, and antioxidant effects of the hydroalcoholic extract of Astragalus ibrahimianus, an endemic plant of Morocco. The analgesic effect was tested using the hot plate, writhing, and formalin tests. The anti-inflammatory activity was assessed by carrageenan and xylene-induced paw/ear edema respectively. The antioxidant activity was evaluated by three tests, namely DPPH, reducing power, and iron chelation. A. ibrahimianus treatment resulted in a significant reduction in carrageenan-induced paw edema and xylene-induced ear edema. Acute pretreatment with the extract reduced the number of abdominal cramps induced by acetic acid injection, increased paw withdrawal latency in the hot plate test, and suppressed both phases of the formalin test. The extract showed significant antioxidant activity regarding the standard molecules. In conclusion, A. ibrahimianus has analgesic, anti-inflammatory, and antioxidant properties.